2022
DOI: 10.1159/000524161
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Burden and Stroke Services in Indonesia

Abstract: Stroke is a major cause of death and disability in Indonesia. Stroke requires high-quality, fast, and precise management to prevent and avoid disability and death. Stroke can be prevented by adequately controlling the risk factors and encouraging healthy lifestyles. Efforts are needed to organize health promotion programs at the community level. More and a better distribution of neurologists and neurointerventionalists is needed. All hospitals should have a CT scan machine and stroke units. Telemedicine for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 11 publications
0
12
0
6
Order By: Relevance
“…Neurosurgeon-to-population ratio is 1:725,000 (371 neurosurgeons), very low compared to the recommended 1:100,000, with the rural community in a greater disadvantage due to its uneven distribution ( 28 ). Over 257 (69.2%) neurosurgeons practices in Java, with most hospitals offering CT scan service, whereas Papua only has five CT scan machines and four neurosurgeons ( 8 , 29 ). North Maluku only has one neurosurgeon and one CT scan machine, of which is located 200 kilometers away from the neurosurgical center.…”
Section: Discussionmentioning
confidence: 99%
“…Neurosurgeon-to-population ratio is 1:725,000 (371 neurosurgeons), very low compared to the recommended 1:100,000, with the rural community in a greater disadvantage due to its uneven distribution ( 28 ). Over 257 (69.2%) neurosurgeons practices in Java, with most hospitals offering CT scan service, whereas Papua only has five CT scan machines and four neurosurgeons ( 8 , 29 ). North Maluku only has one neurosurgeon and one CT scan machine, of which is located 200 kilometers away from the neurosurgical center.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Indonesia and Nepal have also recognized the value of telestroke care, especially considering the difficult terrain in these regions. 31 , 32 …”
Section: Stroke Systems Of Care and Challenges To Stroke Services In ...mentioning
confidence: 99%
“…Studies from India and Indonesia have reported hypertension prevalence of 19.9% and 26.7% among adults, respectively. 9 , 11 Another characteristic finding is the higher prevalence of intracranial atherosclerotic disease, ranging from 20 to 53%, accounting for the high rates of recurrent stroke in the region. A 10-year-long hospital-based registry from South India documented large artery atherosclerosis (LAA) as the most common ischemic stroke subtype, with intracranial atherosclerosis accounting for 78.3% of the LAA subtype.…”
Section: Epidemiologymentioning
confidence: 99%